Analisis Postur Kerja Operator Perakitan di Yessy Shoes untuk Mengidentifikasi Resiko Gangguan Muskuloskeletal Akibat Kerja - Ifen Alfara; Irwan Iftadi; Rahmaniah Dwi Astuti (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2017)
The application of ergonomics in work place is important because the lack of attention can cause health problems to worker, this can be performed by postural assessment using method of visual management, which assessing each elementary operation of a process to the selected domain ergonomics to produce PES (partial ergonomic score) and with a formula then value of OES (overall ergonomic score) is obtaned that shows the operation status of a process. The results obtained from this study is 5 process have value of OES in the range 0.4<OES≤0.5 so operation status is